(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background:Rheumatoid arthritis (RA) is chronic systemic inflammatory disease. Porphyromonus gingivalis (P. gingivalis) produce peptidyle arginine enzymes, which lead to citrullination of human protein then lead to formation anticitrullinated peptide antibody (ACPA). Objective: To investigate the role of P. gingivalis as environmental factor for RA and association of P. gingivalis with development of ACPA. Methods: This study included 31 newly diagnosed RA patients with periodontitis, which included 22 females and 9 men in addition to 30 individual as healthy controls, which included 20 females and 10 men. The exclusion criteria included autoimmune disease (systemic lupus erythematosus, Bachet disease, ankylosing spondylitis, multiple sclerosis), attending Department of Rheumatology in Baghdad Teaching Hospital during period from May 2014 to January 2015. The age range was 20 to 68 years. Disease activity score 28 (DAS28) was calculated for each patient. Five ml of blood sample was taken for detection of ACPA antibody while gingival cervicular fluid was taken by paper point for detection of P. gingivalis by polymerase chain reaction (PCR) with specific primer for fimbrial antigen (fimA). Results:The frequency of positive cases with P. gingivalis were 13/31(41.90%) while in healthy controls was zero with significant P value (